Graphdiyne Interface Engineering: Highly Active and Selective Ammonia Synthesis. Issue 31 (26th May 2020) - Fang, Yan; Xue, Yurui; Li, Yongjun; Yu, Huidi; Hui, Lan; Liu, Yuxin; Xing, Chengyu; Zhang, Chao; Zhang, Danyan; Wang, Zhongqiang; Chen, Xi; Gao, Yang; et al.
Abstract: A freestanding 3D graphdiyne–cobalt nitride (GDY/Co2 N) with a highly active and selective interface is fabricated for the electrochemical nitrogen reduction reaction (ECNRR). Density function theory calculations reveal that the interface‐bonded GDY contributes an unique p‐electronic character to optimally modify the Co‐N compound surface bonding, which generates as‐observed superior electronic activity for NRR catalysis at the interface region. Experimentally, at atmospheric pressure and room temperature, the electrocatalyst creates a new record of ammonia yield rate (Y NH 3 ) and Faradaic efficiency (FE) of 219.72 μg h −1  mgcat. −1 and 58.60 %, respectively, in acidic conditions, higher than reported electrocatalysts. Such a catalyst is promising to generate new concepts, new knowledge, and new phenomena in electrocatalytic research, driving rapid development in the field of electrocatalysis. Abstract : A graphdiyne–cobalt nitride electrocatalyst (GDY/Co2 N) with rationally designed and constructed interface shows high selectivity and efficiency for ammonia synthesis at ambient pressures and room temperature under both acidic and neutral conditions. The unique GDY electronic character plays a critical role for promoting the superior electronic activity and ECNRR performance simultaneously.